Strategies and Best Practices for Implementing Green Campus: A Change Management Reviews - Aedi, Nur (Journal of Ecohumanism, 2024)
The implementation of a green campus is a crucial effort to support environmental sustainability and reduce the carbon footprint of educational institutions. This journal aims to identify strategies and best practices for implementing a green campus using a change management approach. The method used in this study is a literature review, where various scientific articles, reports, and related documents are analyzed to gain a comprehensive understanding of the topic. The results of this study show that the success of green campus implementation depends on several key factors, including the involvement of all stakeholders, management commitment, the provision of adequate resources, and continuous education and training for all campus community members. Additionally, the application of environmentally friendly technologies, energy efficiency improvements, and effective waste management are also essential elements in green campus strategies. This study concludes that a systematic and well-planned change management approach is vital for achieving long-term sustainability goals. These findings are expected to provide practical guidance for educational institutions in designing and implementing effective green campus initiatives.